Sedimentation characteristics of leucocytes can predict bacteraemia in critical care patients. Issue 5 (13th March 2006) - Bogar, L; Molnar, Z; Kenyeres, P; Tarsoly, P
Abstract : Background: Early detection of blood stream infection can be lifesaving, but the results of blood cultures are not usually available before 24 hours after blood sampling. An earlier indication would lead to the initiation of immediate and adequate antibiotic treatment with obvious advantages for the patient. Objective: To evaluate the ability of leucocyte count, serum procalcitonin (PCT) concentration, erythrocyte sedimentation rate (ESR), and leucocyte antisedimentation rate (LAR) in predicting the blood culture results in critical care patients. Methods: 39 consecutive patients with their first febrile episode were investigated prospectively. LAR was determined as the percentage of leucocytes crossing the midline of a blood column upward during one hour of gravity sedimentation. The relevance of the different variables was estimated by likelihood ratio tests and area under receiver operating characteristic curves (AUC). Results: 23 patients had positive blood culture results and 16 negative. LAR was significantly higher in bacteraemic patients than in non-bacteraemic patients (p = 0.001), but leucocyte count, ESR and PCT level failed to show significant differences. Leucocyte count, PCT, and ESR yielded low discriminative values with the AUCs of 0.66, 0.64, and 0.52, respectively. LAR provided a likelihood ratio of 3.6 and an AUC of 0.80 (95% confidence interval, 0.64 to 0.95) (p = 0.002). Conclusions: The simple LAR test can predict blood culture results and support urgent treatment decisions in critical care patients in their first febrile episode.